Infrequent ERBB2 mutations in Chinese patients with non-small cell lung cancer - Feng, Shuidong; Ling, Hongyan; Guo, Hui; Tong, Lingling; Hu, Guobin; Liao, Li; Lv, Xueying; Tan, Hongzhuan; Wu, Yimou (Journal of Thoracic Disease, 2014)
ERBB2 mutations have been reported to occur in a subset of patients with lung adenocarcinomas or lung squamous cell carcinomas for some ethnicities, but it is unclear for Chinese patients with lung squamous cell carcinomas up to now. We retrospectively evaluated the status of ERBB2 mutations in a large cross-sectional cohort of 212 Chinese patients with non-small cell lung cancer (NSCLC) diagnosed in several hospitals from southern China during a time period of 1.5 years by polymerase chain reaction (PCR)- based direct sequencing and PCR-single strand conformation polymorphism (PCR-SSCP) analysis. ERBB2 mutation was found in 1 of 49 lung adenocarcinomas (2.0%) and none in lung squamous cell carcinomas and lung adenosquamous carcinomas. It implies the occurrence of ERBB2 mutations is infrequent in Chinese patients with NSCLC, especially in lung squamous cell carcinomas.